Gender-Related Differences in Pelvic Morphometrics of the Retriever Dog Breed - K. Nganvongpanit (2018)
ï¿½ 2016 Blackwell Verlag GmbH This study presents the results from a morphometric analysis of 52 dry Retriever dog pelvic bones (30 male, 22 female). A total of 20 parameters were measured using an osteometric board and digital vernier caliper. Six parameters were found to be significantly higher (Pï¿½ < ï¿½0.05) in males than in females, while one parameter was significantly higher (Pï¿½ < ï¿½0.05) in females than in males. However, none of the measured parameters demonstrated clear cut-off values with no intersect between males and females. Therefore, we generated a stepwise discriminant analysis from all 20 parameters in order to develop a possible working equationï¿½to discriminate gender from a dog pelvic bone. Stepwise discriminant analysis was used to create a discrimination function: Yï¿½=ï¿½[82.1*PS/AII]ï¿½−ï¿½[50.72*LIS/LI] ï¿½−ï¿½[23.09*OTD/SP]ï¿½+ï¿½[7.69*SP/IE] ï¿½+ï¿½[6.52*IC/OW]ï¿½+ [7.67*ISA/OW] ï¿½+ï¿½[20.77*AII/PS]ï¿½+ï¿½[504.71*OW/ISA] ï¿½−ï¿½[90.84*PS/ISA]ï¿½− [148.95] , which showed an accuracy rate of 86.27%. This is the first study presenting an equation/function for use in discriminating gender from a dog's pelvic measurements. The results can be used in veterinary forensic anthropology and also show that a dog's pelvis presents sexual dimorphisms, as in humans.